2017
DOI: 10.1016/j.ijnss.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Improve nursing in evidence-based practice: How Chinese nurses' read and comprehend scientific literature

Abstract: Objectives To examine Chinese nurses' practice of reading and understanding scientific literature and elucidate the motivating and deterring factors. Methods This is a cross-sectional study conducted between March and June 2015. A random sample of 853 full-time registered nurses from three tertiary and two secondary hospitals in China filled out a set of self-administered questionnaires, including literature habit questionnaire(41 items), the situational motivation scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Öğrenci hemşirelerin araştırma bulgularını kliniğe aktaramamasının nedenleri üzerine yapılan çalışmalara bakıldığında; kanıta dayalı uygulama ile ilgili müfredat ve kaynakların yetersizliği, yabancı dil engeli, makalelerin açık-okunur ve cazip şekilde yazılmaması, araştırma sonuçlarının ulaşılır olmaması, öğrencilerin olumsuz tutumu, bilgi, beceri ve farkındalıklarının az olması, okul-hastane işbirliğinin yetersiz olması ve klinikteki personel ve yöneticilerin KDU bulgularını uygulamaya karşı dirençleri gösterilmektedir. (8,(15)(16)(17)(18) Öğrencilerin, KDU kullanımı için gerekli becerileri (literatür tarama, kanıt değerlendirme, araştırmaları eleştirel analiz edebilme ve araştırma bulgularını klinik uygulamaya aktarılması gibi) kazanmaları, meslek yaşamlarında kolaylık sağlayacaktır. (19) Bununla birlikte, hemşirelik öğrencileri profesyonel hemşirelere kanıta dayalı uygulama bilgilerini aktarabilecek pozisyondadırlar.…”
unclassified
“…Öğrenci hemşirelerin araştırma bulgularını kliniğe aktaramamasının nedenleri üzerine yapılan çalışmalara bakıldığında; kanıta dayalı uygulama ile ilgili müfredat ve kaynakların yetersizliği, yabancı dil engeli, makalelerin açık-okunur ve cazip şekilde yazılmaması, araştırma sonuçlarının ulaşılır olmaması, öğrencilerin olumsuz tutumu, bilgi, beceri ve farkındalıklarının az olması, okul-hastane işbirliğinin yetersiz olması ve klinikteki personel ve yöneticilerin KDU bulgularını uygulamaya karşı dirençleri gösterilmektedir. (8,(15)(16)(17)(18) Öğrencilerin, KDU kullanımı için gerekli becerileri (literatür tarama, kanıt değerlendirme, araştırmaları eleştirel analiz edebilme ve araştırma bulgularını klinik uygulamaya aktarılması gibi) kazanmaları, meslek yaşamlarında kolaylık sağlayacaktır. (19) Bununla birlikte, hemşirelik öğrencileri profesyonel hemşirelere kanıta dayalı uygulama bilgilerini aktarabilecek pozisyondadırlar.…”
unclassified
“…We have read the article entitled “Improve nursing in evidence-based practice: How Chinese nurses' read and comprehend scientific literature” by Huang et al. [1] published in the International Journal of Nursing Sciences. We would like to appreciate and strongly support the authors' efforts in pointing out the importance of Evidence-Based Practice (EBP) in nursing.…”
mentioning
confidence: 99%
“…As a professional, nurses need to use evidence-based intervention and the integration of research findings into practice [2,3]. EBP is an approach to nursing care that is very important for improving patient outcomes [4], however, the previous studies have been suggested that health professional does not always use the evidence to guide their practice [1,[5], [6], [7]]. Huang et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations